Aqueous Extract of Purple Sweet Potato Tubers Decrease MDA and Increase SOD2 in Kidney of Diabetic Rats - Satriyasa, Bagus Komang (BALI MEDICAL JOURNAL; Vol 5 No 3 (2016), 2016)
Diabetes mellitus (DM) is a metabolic disease characterized by increase of blood glucose levels or hyperglycemia. Hyperglycemia results in oxidative stress and increase of AGEs. Oxidative stress and metabolic stress lead to reduction of endogenous antioxidant activity resulted in various organs injury especially kidney. The complication is caused by the formation of advanced glycation end products (AGEs), and free radicals. Increase free radicals that occur in diabetics accompanied with decline in endogenous antioxidant activity, such as superoxide dismutase (SOD) and catalase. One way to overcome the complications due to oxidative stress is through utilize the foods which possess natural antioxidant such as purple sweet potato. It has been proven in animals that purple sweet potato had antioxidant properties to prevent various complications in DM. Balinese purple sweet potato tubers contain high anthocyanin and it had been researched as antioxidant in rats in vivo. The aims of this research are to determine the effect of aqueous extract of purple sweet potato tubers to decrease malondialdehyde (MDA) and increase SOD2 in kidney of diabetic rats. This experimental study was conducted with randomized posttest only control group design. Research subject is 38 diabetic rats that divided into 2 groups, controlled group and treatment group, with 18 diabetic rats in each group. Treatment was given for 60 days to each group. Treatment group (P1) is diabetic rats group that was given a standard diet and ad libitum drinks, and 4CC/day/rat of purple sweet potato tubers aqueous extract for 60 days. Controlled group (P0) is diabetic rats group as control that was given a standard diet and ad libitum drinks only. After 60 days of treatment, evaluation was performed. The results of this research found that mean MDA in kidney of control and treatment group was 8.40?0.17 and 1.47?0.15, respectively. There was a significant decreae of MDA (p<0.05). Relative expression of SOD2 gene before and after treatment was 0.317 and 6.586, respectively. There was a significant increase of SOD2 gene (p<0.05). It can be concluded that aqueous extract of purple sweet potato tubers decrease MDA and increase SOD2 gene in kidney of diabetic rats.
Keywords: Aqueous extract of purple sweet potato tubers, MDA, SOD2, kidney, diabetic rats